Insights into Otitis Media: Dissecting the interaction of C-Reactive Protein with Non-Typeable Haemophilus influenzae. Issue 5 (27th May 2022) - Bharj, Gurpreet; Vikhe, Pratik; Brown, Steve; Hood, Derek
Abstract : Otitis Media (OM) is the inflammation of the middle ear (ME). Non-typeable Haemophilus influenzae (NTHi) is one of the leading otopathogens in causing OM. Phosphocholine (PCho) on the NTHi lipopolysaccharide influences host-pathogen interaction. C-Reactive Protein (CRP), an acute phase protein recognizes PCho, and can mediate bacterial killing. However, some strains of NTHi survive even in the presence of CRP. We aim to study the interaction of CRP with NTHi to understand its role in bacterial survival and OM. NTHi can efficiently infect the Junbo mouse, a characterised model of chronic and acute OM. CRP levels were highest 1 day post-intranasal inoculation in the ME fluid (MEF) and nasal passage (NP) washes. We show CRP is a localized response to NTHi as serum CRP levels were unaffected in NTHi inoculated and non-inoculated mice at 1, 3 and 7-day post intranasal inoculation. Further, we confirm the presence of NTHi influences CRP levels in the MEF and NP washes. We show CRP binding is influenced by the position and expression of PCho on the NTHi surface. Serum bactericidal assays indicate that the expression and position of PCho affects NTHi survival. The removal of CRP from the serum restores NTHi survival. The expression of PCho also influences opsonophagocytosis activity in macrophages, thereby confirming the importance of PCho in NTHi survival. The CRP-NTHi interaction is currently under investigation to advance our understanding of its role in the complex biological processes that influence bacterial killing and the onset, progression and resolution of OM caused by NTHi.